International trade problems of small nations - Lloyd, Peter John (North Carolina : Duke university press, 1968)
This book explore the question: is it possible to develop a theory, or sets of theories of small nations trading?
includes index
ijb, 16/01/2019
Loans
Keywords: Small nations; International Trade